Study of utilization of antenatal care services and its determinants among pregnant women admitted in a tertiary care hospital in Mangaluru, Karnataka, India - Kumar, Hemant; Chacko, Iybu V.; Mane, Seema; N. Govindan, Narayanan; Prasanth, Sneha (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally only 64% of women receive antenatal (prenatal) care four or more times throughout their pregnancy. National family health survey (NFHS) -4, brings out that in India, 21% of pregnant women utilized full ANC, ranging from 2.3-65.9% across the states. Quality health care during pregnancy and childbirth can prevent many pregnancy related deaths. The objective of the present study was to examine utilization of antenatal care services among the study subjects and find out its determinants, including out of pocket expenditure incurred on management of the pregnancies. Methods: The study was conducted in a tertiary care teaching hospital among full term pregnant mothers and those who had recently delivered. Purposive sampling method was used and sample size of 368 was calculated. Results: The study brought out that 100% women had their registration, 75.5% of them within 12 weeks of pregnancy. Majority of the women (69.5%) preferred private health care facility clinic for antenatal check-up. However, the utilization of various government schemes in place for the benefit of pregnant mothers were underutilized (26.6%).The study also revealed that 16.0% of the families suffered catastrophic expenditure as the cost of treatment on antenatal care and treatment went beyond household budget and they had to borrow money for the treatment. Conclusions: A significant association was found between number of antenatal visits and increasing age, higher socio-economic status, higher educational status, Hindu religion, place of residence (urban), nuclear type of family and early registration.